Influence Of Training, Workplace Environment, Motivation, And Compensation Towards Employee Performance In Company PT Oto Makmur Gemilang - Davin Kurniawan; Ari Mulianta Ginting (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
This study aims to examine the influence of human resource dimensions in affecting employee performance as crucial development for a company. The human resource dimensions mentioned are training, motivation, workplace environment and compensation. The research was conducted using quantitative methods with 150 respondents using Partial Least Square and Structural Equation Modeling (PLS-SEM). This study shows that the Employee Performance variables, which are examined through questionnaires and hypothesis testing using SmartPLS-SEM, have a direct influence on employee performance.